PEMBELAJARAN BERBANTUAN MEDIA SAKU GANTUNG DAN SEDOTAN UNTUK MEMAHAMKAN TEKNIK MENYIMPAN DAN MEMINJAM DALAM OPERASI BILANGAN CACAH PADA SISWA KELAS II SEKOLAH DASAR - Mufarrahatus Syarifah; Gatot Muhstyo; I Nengah Parta (Universitas Bondowoso, 2021)
The aim of this study is describing instructional process using straws and hanging pocket as instructional media which make the students understand on saving and borrowing techniques in operation with whole number. Instructional process using straws and hanging pocket as instructional media had increased students’ interest and enthusiasm during the instruction. In addition, through the activity with straws and hanging pocket, students were involved in composing algorithms of saving and borrowing techniques so that they remembered these algorithms easily and retained longer. Despite of final test results showed that the criteria of success was not met, the students who failed on the test could solve saving and borrowing techniques problems and explained how they worked well. This condition indicated that the student basically had understood how to apply the saving and borrowing techniques well as a result of using straws and hanging pocket as instructional media.